Wooden Beginnings, Human Struggles: Pinocchio’s Character Development Through Erikson’s Psychosocial Stages - Tano, Andreas; Warouw, Carissa Florenze Isabelle; Martin, Violet Ayuwandira Larasati (Jurnal Pendidikan Makarios, 2025)
This study analyzes Carlo Collodi’s Pinocchio through Erik Erikson’s psychosocial development theory to trace the character’s psychological growth across childhood stages. Using qualitative, descriptive analysis, the research examines how Pinocchio’s experiences embody Erikson’s developmental crises. The results reveal three key findings: 1) Pinocchio’s disobedience and peer influence illustrate Autonomy vs. Shame and Doubt, reflecting a child’s struggle for independence under external pressures. 2) His refusal to heed guidance highlights Initiative vs. Guilt, as he experiments with choices but risks moral error. 3) His eventual responsibility and care for Geppetto demonstrate Industry vs. Inferiority, showing his attainment of competence and integrity. Pinocchio’s transformation into a real boy symbolizes the successful resolution of these crises, affirming Erikson’s claim that growth emerges from overcoming challenges. This study concludes that Pinocchio reflects universal childhood struggles and offers psychological insight into moral and social development.